Single vs multiple fraction palliative radiation therapy for bone metastases: Cumulative meta-analysis. (December 2019) - Chow, Ronald; Hoskin, Peter; Schild, Steven E.; Raman, Srinivas; Im, James; Zhang, Daniel; Chan, Stephanie; Chiu, Nicholas; Chiu, Leonard; Lam, Henry; Chow, Edward; Lock, Michael
Highlights: All but one endpoint maintained the same meta-conclusion over publication time. New studies did not change the scientific conclusion of existing literature. SFRT is equally as efficacious as MFRT. The majority of included studies have low risk of bias. Future resources should not be used to repeat these studies, and can be better allocated to test other hypotheses. Abstract: Introduction: There has been a long-standing debate regarding the efficacy of single fraction radiotherapy (SFRT) compared to multiple fraction radiotherapy (MFRT); many systematic reviews and meta-analyses have been conducted to resolve the debate and suggested SFRT is equally as effective as MFRT. Given the adequate amalgamated sample size that exists, it is difficult to appreciate the need for further RCTs. The aim of this paper was to conduct a cumulative meta-analysis to determine whether further trials will be of value to the meta-conclusion. This paper also assessed publication quality. Methods: A total of 29 studies were used in our meta-analysis. Comprehensive Meta-Analysis (Version 3) by Biostat was used to conduct a cumulative meta-analysis. The Cochrane Risk of Bias assessment tool was employed to assess study quality of the included RCTs. Funnel plots were generated using Review Manager (RevMan 5.3) by Cochrane IMS, to visually assess for publication bias. Results: All but one endpoint, overall response rates in assessable patients, maintained the same meta-conclusion over publication time; published studies did not change the amalgamated scientific conclusion of existing literature. Additional studies have simply confirmed pre-existing conclusions and refined the point estimate of the efficacy estimate. The majority of included studies have low risk of bias. Conclusion: In conclusion, the meta-conclusion has remained consistent over time – SFRT is equally as efficacious as MFRT. Recent studies have had little impact on the overall conclusion, and given the vast amount of resources to execute a randomized trial, future resources should not be used to repeat these studies, and can be better allocated to test other hypotheses.